Analisis Efisiensi Teknis Usahatani Gambir di Kabupaten Pesisir Selatan Menggunakan Model Kumbhakar - Mizi Sasrido; Faidil Tanjung; Vonny Indah Mutiara (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Gambir is a leading plantation commodity that has high economic value and is widely cultivated by farmers in West Sumatra. Pesisir Selatan Regency is the second producer of gambier in West Sumatra. Gambier farming in Pesisir Selatan Regency is still facing various obstacles, one of which is technical constraints, namely the low productivity of gambir in the period 2016 to 2020. This study aims to analyze technical efficiency and identify sources of technical inefficiency in gambir farming in Pesisir Selatan Regency. The survey was conducted on 60 samples of farmers who carried out harvesting and processing of gambir sap in the period January-December 2021 and the samples were selected by non-probability sampling. The analytical tools used are the frontier productivity function model, production risk function and technical inefficiency function developed by Kumbhakar. The result of this research is the average technical efficiency of gambier farming in Pesisir Selatan Regency is 0.83. This shows that gambier farming is technically efficient. Based on the analysis of sources of inefficiency, it is found that other sources of income and land ownership status can significantly reduce technical inefficiency.